An ultrastructural approach for gill responses after pollutants exposure - Pereira, Bruno Fiorelini; Pitol, Dimítrius Leonardo; Caetano, Flávio Henrique [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
Morphological and physiological responses of gills exposed to environmental contaminants are widely described in the literature. Among the primary findings are the lamellar fusion, hyperplasia, aneurysms, proliferation of mitochondria-rich cells and mucous cells. This work has as main objectives, to show the main changes caused by a polluted lake in gills, and understand how each gill's cell type responds to pollutants' exposure. To those individuals of the species, Astyanax altiparanae were exposed to water from an urban lake, which receives such contaminants from various sources. The gills were analyzed under a TEM. Our results showed that prior to these changes, commonly found, only the mucous cells did not show structural changes. Among the main results, we observed the emergence of Rodlet cells in the group exposed to contaminants, as well as severe damage to the mitochondria-rich cells.The latter result was extremely relevant for demonstrating that the proliferation of this cell type, widely described as an alternative ionic regulation, may in some cases be completely inefficient because structurally these cells are no longer able to perform their basic metabolic functions.
Un enfoque ultraestructural de las respuestas branquiales después de la exposición a contaminantes
Keywords: Astyanax; Gill; Ultrastructure; Water pollution